The relationship between frontal QRS‐T angle and the severity of newly diagnosed chronic obstructive pulmonary disease. Issue 10 (29th June 2021) - Hocanli, Iclal; Tanriverdi, Zulkif; Kabak, Mehmet; Gungoren, Fatih; Tascanov, Mustafa Begenc
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is characterised by persistent airflow restriction and respiratory symptoms. Studies demonstrated that cardiac arrhythmias and cardiovascular mortality increased in these patients as a result of altered myocardial repolarization. Frontal QRS‐T angle is a novel marker of myocardial depolarization and repolarization heterogeneity. In this study, we aimed to investigate the relationship between frontal QRS‐T angle and disease severity in patients with newly diagnosed COPD. Methods: A total of 104 newly diagnosed COPD patients were included in this study. Patients were divided into two groups according to GOLD (Global Obstructive Lung Disease) stage as follows: patients with mild and moderate COPD (group I), and severe and very severe COPD (group II). Frontal QRS‐T angle was calculated from the automatic report of the electrocardiography device. Results: Frontal QRS‐T angle was significantly higher in group II patients compared with in group I patients (43.0 [25.5‐60.0] vs. 20.0 [12.0‐32.0], P < .001). The best cut‐off value of frontal QRS‐T angle for predicting severe‐very severe COPD was ≥34.5°. Correlation analysis showed that frontal QRS‐T angle was negatively correlated with FEV1/FVC ( r = –.524, P < .001) and MEF25‐75 ( r = –.453, P < .001). Multivariate logistic regression analysis was showed that frontal QRS‐T angle was the only independent predictor of severe‐very severe COPD (OR: 1.051, 95% CI: 1.024‐1.079, P < .001). Conclusions: Frontal QRS‐T angle is an easily obtainable marker form surface electrocardiography. In this study, we have shown for the first time that frontal QRS‐T angle was significantly increased in patients with severe and very severe COPD.